Relationships between psychosocial outcomes in adolescents who are obese and their parents during a multi-disciplinary family-based healthy lifestyle intervention: One-year follow-up of a waitlist controlled trial (Curtin University's Activity, Food and Attitudes Program) - Fenner, Ashley; Howie, E.; Davis, M.; Straker, L. (BioMed Central Ltd., 2016)
Background: Limited studies have investigated relationships in psychosocial outcomes between adolescents who are obese and their parents and how psychosocial outcomes change during participation in a physical activity and healthy eating intervention. This study examined both adolescent and parent psychosocial outcomes while participating in a one - year multi-disciplinary family-based intervention: Curtin University’s Activity, Food, and Attitudes Program (CAFAP). Methods: Following a waitlist control period, the intervention was delivered to adolescent (n = 56, ages 11–16) and parent participants over 8 weeks, with one-year maintenance follow-up. Adolescent depression and quality of life, family functioning, and parent depression, anxiety, and stress were assessed at six time points: baseline and prior to intervention (e.g., waitlist control period), immediately following intervention, and at 3, 6, and 12 months post-intervention. Relationships between adolescent and parent psychosocial outcomes were assessed using Spearman correlations and changes in both adolescent and parent outcomes were assessed using linear mixed models. Changes in adolescent psychosocial outcomes were compared to changes in behavioural (physical activity and healthy eating) and physical (weight) outcomes using independent samples t-tests.Results: The majority of psychosocial outcomes were significantly correlated between adolescents and parents across the one-year follow-up. Adolescent depression, psychosocial and physical quality of life outcomes significantly improved before or following intervention and were maintained at 6-months or one-year follow-up. Parent symptoms of depression, anxiety, and stress were reduced during waitlist and primarily remained improved. Changes in adolescent psychosocial outcomes were shown to be partially associated with behavioural changes and independent of physical changes. Conclusions: Adolescents in CAFAP improved psychosocial and physical quality of life and reversed the typical trajectory of depressive symptoms in adolescents who are obese during a one-year maintenance period. CAFAP was also effective at maintaining reductions in parent symptoms of depression, anxiety, and stress demonstrated during the waitlist period. Trial Registration: The trial was registered with the Australian and New Zealand Clinical Trials Registry (No. 12611001187932).